THE INFLUENCE OF WORK TRAINING, TEAMWORK, WORK MOTIVATION, AND WORK DISCIPLINE ON WORK PERFORMANCE AT PT PLN (PERSERO) UP 3 MEDAN - Derry Alamsyah Lubis; Fajar Rezeki Ananda Lubis; Leonardo; Vira Fidellia; Thezar Fiqih Hidayat Hasibuan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The objective of this study is to analyze the influence of training, teamwork, work motivation, and work discipline on job performance at PT. PLN (Persero) UP 3 Medan. This research is quantitative in nature. The population consists of all employees from PT. PLN (Persero) UP 3 Medan, totaling 50 employees. The sample size matches the population size, comprising 50 employees, selected using saturated sampling technique. The research findings indicate that H1 is accepted, indicating that training influences job performance at PT. PLN (Persero) UP 3 Medan. H2 is accepted, indicating that teamwork influences job performance at PT. PLN (Persero) UP 3 Medan. H3 is accepted, indicating that work motivation influences job performance at PT. PLN (Persero) UP 3 Medan. H4 is accepted, indicating that work discipline influences job performance at PT. PLN (Persero) UP 3 Medan. H5 is accepted, indicating that training, teamwork, work motivation, and work discipline collectively influence job performance at PT. PLN (Persero) UP 3 Medan.